The Effect of Service Quality And Facilities on Customer Satisfaction - Ferdinandsyah, Azka; Fadili, Dadan Ahmad (Peneliti.net, 2024)
Abstract Consumer satisfaction at Villa Cemara Situ Gunung can be influenced by many factors, including the quality of service and facilities. The existence of good service quality and complete facilities can certainly increase consumer satisfaction. This research aims to determine the influence of Service Quality and Facilities on Consumer Satisfaction at Villa Cemara Situ Gunung. The research method used is a descriptive verification method with a quantitative approach. The test stages used are validity test, reliability test, classical assumption test, multiple linear regression analysis technique and hypothesis testing using the t test, f test and coefficient of determination using SPSS 25 tools with the main data source being questionnaires distributed to consumers who are staying overnight. at Villa Cemara in 2023 there will be 230 respondents. The results of the descriptive analysis show that Service Quality has a total average score of 822.2 which is included in the